Solid-liquid phase equilibrium: in search of suitable PCMs for low temperature energy storage - Sequeira, Maria Carolina (2022)
Centro de Química Estrutural is a Research Unit funded by Fundação para a Ciência e Tecnologia through projects UIDB/00100/2020 and UIDP/00100/2020. • Institute of Molecular Sciences is an Associate Laboratory funded by FCT through project LA/P/0056/2020. • M.C.M. Sequeira acknowledges the PhD grant funded by FCT ref. UI/BD/152239/2021.